2019
DOI: 10.1002/mas.21595
|View full text |Cite
|
Sign up to set email alerts
|

MS1 ion current‐based quantitative proteomics: A promising solution for reliable analysis of large biological cohorts

Abstract: The rapidly‐advancing field of pharmaceutical and clinical research calls for systematic, molecular‐level characterization of complex biological systems. To this end, quantitative proteomics represents a powerful tool but an optimal solution for reliable large‐cohort proteomics analysis, as frequently involved in pharmaceutical/clinical investigations, is urgently needed. Large‐cohort analysis remains challenging owing to the deteriorating quantitative quality and snowballing missing data and false‐positive di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 237 publications
(308 reference statements)
0
48
0
Order By: Relevance
“…Exploring recently developed MS1 ion current-based proteome analysis will lead to a more comprehensive repertoire of the proteins, although this study has reported on more than 800 proteins in the rootlet proteome [48]. One of the most important limitations in analyzing omics dataset is the availability of well-annotated genomes.…”
Section: Discussionmentioning
confidence: 97%
“…Exploring recently developed MS1 ion current-based proteome analysis will lead to a more comprehensive repertoire of the proteins, although this study has reported on more than 800 proteins in the rootlet proteome [48]. One of the most important limitations in analyzing omics dataset is the availability of well-annotated genomes.…”
Section: Discussionmentioning
confidence: 97%
“…Its greatly enhanced sensitivity and specificity could be demonstrated for a broad spectrum of published and newly generated data sets demonstrating its universal applicability. Although it had been previously shown that DICE-based data analysis has highly attractive performance features 1 , IceR is the first to offer this as a comprehensive yet userfriendly R-package. In addition, since DDA-based proteomics is widely used and firmly established, having undergone many rounds of methodological and hardware optimization over the last decade, and since IceR can be readily integrated in existing workflows, we expect that IceR can be easily adopted and that it will be of great value for the proteomics community.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, false transfers cannot be excluded, requiring specific attention 23 . In contrast, ion-based PIP applies direct ion current extraction (DICE), and only requires the existence of ions within a given retention time and mass-to-charge window, thus enabling sensitive identity propagation 1 . Ion-based PIP has been implemented in DeMix-Q 8 and IonStar 12 , both achieving highly reduced missing value rates and improved sensitivity to detect differentially abundant proteins compared to MaxQuant.…”
Section: Introductionmentioning
confidence: 99%
“…Conventional 2-DE is now obsolete, with quantitative proteomics MS techniques offering a far better sensitivity of detection, the capability for high-throughput whole proteome analysis in a single MS run and the quantitative comparison of multiple experimental conditions in a single experiment. Quantitative proteomics MS techniques are broadly divided into label-free quantification (LFQ) methods, such as MS1-intensity based methods 50 and spectral counting-based methods, 51 and several different labelling-based methods. Popular labelling strategies include TMT (tandem mass tag), 52 iTRAQ (isobaric tagging for relative and absolute quantitation), 53 SILAC (stable isotope labelling by amino acids in cell culture) 54 and stable isotope dimethyl labelling.…”
Section: Proteomics Approaches In Leishmaniamentioning
confidence: 99%
“…Both SAMS and SAHH play key roles in the pathways upstream of the biosynthesis of trypanothione, a unique thiol metabolite of Kinetoplastida that is implicated in antimony resistance and the parasite's response to oxidative stress. 48 50 and spectral counting-based methods, 51 and several different labelling-based methods. Popular labelling strategies include TMT (tandem mass tag), 52 iTRAQ (isobaric tagging for relative and absolute quantitation), 53 SILAC (stable isotope labelling by amino acids in cell culture) 54 and stable isotope dimethyl labelling.…”
Section: Tracking Variations In the Parasite Proteome For The Molecular Characterisation Of Key Life Processesmentioning
confidence: 99%